Optical and photoluminescence properties of Ga doped ZnO nanostructures by sol-gel method - Phan, D. -T.; Farag, A. A. M.; Yakuphanoğlu, Fahrettin; Chung, G. S. (Springer, 2012)
Zinc oxide (ZnO) nanocrystallites with different Ga-doping levels were successfully prepared by spin coating sol-gel technique. The morphological properties of Ga doped ZnO films were studied by atomic force microscopy (AFM). Alignment of ZnO nanorods with respect to the substrate depends on the amount of Ga dopant content. The dopant content varies from 1 % to 4 %, based on Ga-doping levels. The optical properties of the ZnO nanocrystallites following Ga-doping were also investigated by UV-Visible absorption and Photoluminescence spectra. Our results indicate that Ga-doping can change the energy-band structure and effectively adjust the intensity of the luminescence properties of ZnO nanocrystallites. Transmittance spectra of the films indicate that the films have high transparency. The refractive index dispersion was analyzed by single oscillator model developed by Wemple and DiDomenico. The oscillator energy, dispersion energy, high frequency dielectric constant values for the films were determined were calculated and it is found that the optical parameters are changed with Ga-doping content.
Keywords: Ga-doped ZnO; Photoluminscence; nanorods; Optical dispersion